TOWARD INDONESIA’S ZERO LEPROSY 2030: KEY LESSONS FROM EPIDEMIOLOGICAL TRENDS IN PAPUA 2020-2024 - Sumolang, Inneke Viviane; Romadhon, Dimas Iqbal; Suyanto, Agnes Angelita (Folia Medica Indonesiana, 2025)
Papua, the easternmost province of Indonesia, has consistently reported the highest number of new leprosy cases and leprosy-related disabilities for decades. Despite this burden, no comprehensive study in recent years has systematically examined the epidemiological trends of leprosy in Papua using large datasets. This study provides an updated analysis of leprosy elimination efforts and evaluates the province’s readiness to achieve the Zero Leprosy 2030 target. A retrospective descriptive epidemiological review was conducted using secondary data from the routine health information system of Papua Province from 2020 to 2024. Extracted variables included demographic characteristics, new case reports, diagnostic classification, disability grade, case-finding method, and clinical outcomes. Data were analyzed descriptively and presented in tables and figures to illustrate temporal trends. Between 2020 and 2024, a total of 3,909 new leprosy cases were reported, with fluctuating case detection rates. Multibacillary (MB) leprosy predominated, particularly among males, although females also contributed a substantial proportion of MB cases. Child cases showed an increasing trend, accounting for up to 20% of all new cases. Most cases were detected at Grade 0, with passive case finding as the dominant detection method. Treatment outcomes showed that approximately 70% of patients were released from treatment annually, but relapse and default remained considerable. These findings highlight that Papua is still far from reaching the Zero Leprosy 2030 goal. Strengthening active case finding, improving treatment adherence, reducing stigma, and enhancing reporting and evaluation systems are urgent priorities. Sustained political commitment from local leadership will be crucial to ensure the successful implementation of these strategies.